A review on high pressure processing of food - Kumar, Sanoj; Kumar, Pankaj (Journal of Postharvest Technology, 2019)
The quality and safety of food products are the two factors that most influence the choices madeby today’s increasingly demanding consumers. Conventional food sterilization and preservationmethods often result in a number of undesired changes in foods, such as loss of smell, colour, flavour, texture and nutritional value – in short, a reduction in the apparent freshness and quality of the final product. High-pressure (HP)  processing, also sometimes known as high hydro- static pressure (HHP), or ultra high pressure (UHP) processing, is a relatively new non thermalfood processing method that subjects liquid or solid foods, with or without packaging, to pres-sures between 50 and 1000 MPa. Extensive investigations have revealed the potential benefits of high pressure processing as an alternative to heat treatments. These benefits are apparent in various areas of food processing, such as the inactivation of microorganisms and enzymes, denaturation and alteration of the functionality of proteins and structural changes to food materials.
Keywords: Food processing; consumer; high pressure; pressure-shift; food safety